Mózg i Sztuka: zmarszczka (cyber)przestrzeni - Hoffmann-Dietrich, Joanna (Poznańskie Studia Polonistyczne. Seria Literacka, 2019)
In my text I refer to contemporary art practices, including my own artistic investigations and intuitions; questioning creative powers of the human brain-mind system in the world increasingly dependent on and transformed by Big Data. Currently, with the global revolution of knowledge, driven by scientific and technological progress, creativity and innovation acquire special economic and social values. Research on biochemical processes accompanying creative behaviour stimulates the synergy between artistic, scientific and engineering communities. The acquired knowledge is used in medicine, biotechnology and various types of therapies as well as in deep learning methods. Increasing the efficiency of artificial intelligence systems that quickly take control over all areas of our lives. Will the nascent Internet-of-all-Things transform itself into the Internet-of-all Minds? As an artist, I pose myself a question, which artistic practices may emerge from the marriage of biological and digital algorithms? The future has many scenarios and shades…